2008
DOI: 10.1017/s1352465808004451
|View full text |Cite
|
Sign up to set email alerts
|

Empirically Grounded Clinical Interventions: Cognitive Versus Behaviour Therapy in the Individual Treatment of Obsessive-Compulsive Disorder: Changes in Cognitions and Clinically Significant Outcomes at Post-Treatment and One-Year Follow-Up

Abstract: Clinical significance analyses of controlled studies comparing Exposure and Response Prevention (ERP) and Cognitive Therapy (CT) in the treatment of Obsessive-Compulsive Disorder (OCD) are scarce. The objective of this study is to compare the clinical efficacy of ERP and CT for OCD patients, and the usefulness of each in changing dysfunctional beliefs and thought control strategies at post-treatment and at a one-year follow-up. The two treatments were delivered on the basis of a routine clinical practice in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 59 publications
8
25
0
1
Order By: Relevance
“…Our results coincide especially with those obtained in the latter study. We also observed that the symptom reduction after CT could be extended to depression and worry, as found in Belloch, Cabedo, and Carrió (2008). The changes in depression could be attributable, on the one hand, to the fact that Depression was secondary to OCD and, on the other hand, to the effects of pharmacotherapy for both OCD and depression, given that in most cases both disorders receive the same treatment (e.g., serotonin reuptake inhibitors or selective serotonin reuptake inhibitors).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our results coincide especially with those obtained in the latter study. We also observed that the symptom reduction after CT could be extended to depression and worry, as found in Belloch, Cabedo, and Carrió (2008). The changes in depression could be attributable, on the one hand, to the fact that Depression was secondary to OCD and, on the other hand, to the effects of pharmacotherapy for both OCD and depression, given that in most cases both disorders receive the same treatment (e.g., serotonin reuptake inhibitors or selective serotonin reuptake inhibitors).…”
Section: Discussionsupporting
confidence: 58%
“…The tendency to suppress thoughts (WBSI) and the strategy of selfpunishment (TCQ) for having "bad" thoughts were also significantly decreased after treatment, and these results were maintained at follow-up. Changes in dysfunctional beliefs and thought control strategies have also been reported after successful psychological treatments for OCD, irrespective of the subtypes or modalities (e.g., Abramowitz, Franklin, et al, 2003;Abramowitz, Whiteside, et al, 2003;Belloch et al, 2008;Whittal et al, 2005;Wilhelm et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There is one evaluation that suggests exposure alone produces significant change in the cognitions associated with the disorder, regardless of symptom type. In Belloch et al (2008), with a sample of 33 individuals with OCD randomly assigned to either ERP or CT alone, the authors found significant improvement in both groups, with slightly better outcome for CT. However, of particular note in this case is that both groups showed similar levels of improvement on measures of appraisals (evaluated with the Obsessive Beliefs Questionnaire-44 (OBQ-44), Obsessive Compulsive Cognitions Workgroup, 2005) associated with OCD.…”
Section: Variations In Treatment Implementationmentioning
confidence: 95%
“…Simpson et al (2006) reported that 37% (seven out of 19) of patients who received 3 months of cognitive behavior therapy (CBT) plus Anafranil had recovered. Belloch et al (2008) examined the efficacy of 6 months of ERP compared with cognitive therapy with 29 OCD patients. Also using the post-treatment criteria of YBOCS r7 (and at least six points improvement), 8/13 (61.53%) in the ERP condition and 11/16 (68.75%) were recovered at posttreatment.…”
Section: Durability Of Treatment Gainsmentioning
confidence: 99%
“…This variable ranged from 0.7 (Belloch et al, 2008) to 10.0 (Lindsay et al, 1997) hours/week with a mean of 3.2 (SD 3.3). Here too the two internetbased CBT studies had the lowest values with 0.2 hours, i.e.…”
Section: Accepted Manuscriptmentioning
confidence: 99%